Knowledge, science and reletavism: Philosophical papers: Volume 3 - Feyerabend, Paul; Preston, John (New York Cambridge University Press, 1999)
This third volume of Paul Feyerabend's philosophical papers, which gathers together work originally published between 1960 and 1980, offers a range of his characteristically exciting treatments of classic questions in the philosophy of science, including theoretical pluralism, the relationship between theory and observation, the distinction between science and myth, the role of science in society, and the vexed question of the nature of scientific method. The volume is completed by a substantial introduction and a comprehensive list of Feyerabend's works.